Brazing filler metal composition and welding method
By covering the Ni-B alloy layer on the surface of the silver-based brazing powder and generating TiB whiskers, the residual stress problem of ceramic/metal components in traditional active brazing connections is solved, and a high-strength and low-stress welding effect is achieved.
Patent Information
- Application Number
- CN202510217238.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-04
AI Technical Summary
Large-size complex structural ceramic/metal components have large residual stresses in traditional active brazing connections, resulting in low joint strength and easy cracking.
Using a first silver-based brazing powder and a second silver-based brazing powder composition covered with a Ni-B alloy layer, TiB whiskers are generated by in-situ reaction of the Ni-B alloy layer with Ti in the liquid brazing material to form a non-uniform mesh pinning structure to coordinate matrix deformation and adjust the coefficient of thermal expansion of the weld.
It realizes the welding effect of simple joint structure, high strength and low residual stress, and is especially suitable for the welding of large-size complex structural ceramic-metal composite components.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of welding, in particular to a solder composition and a welding method. Background Art
[0002] Ceramic-metal heterogeneous components are widely used in aerospace, nuclear energy, electronics and other fields, and active brazing is one of the main methods to achieve metallurgical connection of heterogeneous materials. Active brazing uses brazing materials containing active elements such as Ti, Zr, and Ni for brazing connection, which effectively solves the problem that liquid metal brazing materials are difficult to wet on the ceramic surface. However, for large-scale and complex-structure ceramic / metal components, due to the large difference in the physical properties of ceramics and metals, components connected by traditional active brazing often have large residual stresses, resulting in low joint strength and easy cracking.
[0003] At present, active brazing technology is mainly used for ceramic / metal connection. Active brazing is to add active elements such as Ti, Zr, Ni to the brazing filler metal, and use the reaction between the active elements and ceramics to promote the wetting of the liquid brazing filler metal on the ceramic surface. Active brazing technology overcomes the problem that the metal brazing filler metal does not wet the ceramic surface, but it cannot effectively reduce the residual stress after ceramic-metal welding. In order to reduce the residual stress of ceramic-metal welded joints, the commonly used methods based on active brazing technology include buffer layer method and composite brazing filler metal method. The buffer layer method is to set high plasticity metals such as Cu and Ni or low thermal expansion coefficient metals such as Mo, Nb, and W in the welded joint to release or adjust the residual stress; this method is simple and effective, but the introduction of the metal layer will bring multiple welding interfaces and complex joint structure. The composite solder method is to mechanically mix low thermal expansion coefficient materials, such as ceramic particles such as SiC, Al2O3, or metal particles such as Mo and W, into the active solder, and use the mixed external reinforcement phase to adjust the thermal expansion coefficient of the joint; the disadvantage of this method is that impurities are easily introduced during the mixing process, and the external phase reacts with the active solder to easily generate brittle intermetallic compounds, making the joint brittle. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is a solder composition and a welding method. The solder composition provided by the present invention forms a joint with a simple structure, high strength and low residual stress.
[0005] The present invention provides a solder composition, comprising:
[0006] 10 wt.% to 40 wt.% of a first silver-based solder powder having a Ni-B alloy layer coated on the surface;
[0007] 1 wt.%~5 wt.% Ti powder;
[0008] the balance of the second silver-based solder powder;
[0009] The first silver-based solder powder and the second silver-based solder powder are independently selected from one or more of AgCu or AgCuTi.
[0010] Preferably, the first silver-based solder powder and the second silver-based solder powder of the present invention are the same. More preferably, the first silver-based solder powder and the second silver-based solder powder of the present invention are both selected from AgCu; or, the first silver-based solder powder and the second silver-based solder powder are both selected from AgCuTi.
[0011] The solder composition provided by the present invention comprises a first silver-based solder powder with a Ni-B alloy layer coated on the surface, specifically comprises a spherical first silver-based solder powder with a Ni-B alloy layer coated on the surface, which is an active solder powder with a core-shell structure. The core-shell structure of the first silver-based solder powder coated with the Ni-B layer can prevent the first silver-based solder powder from agglomerating in the liquid phase and extruding from the weld. Because the first silver-based solder powder such as Ag-Cu or AgCuTi has a low liquid phase melting point and good fluidity, it will aggregate together and be extruded from the weld at high temperature if not restricted, so that only the Ti-Cu alloy is left in the weld. According to the Ag-Cu-Ti ternary phase diagram, there is a miscibility gap between the Ag-based solid solution and the Ti-Cu phase, that is, under uncontrolled conditions, the Ag-based solid solution will be "stratified" with the Ti-Cu liquid phase (like water and oil), and the continuously distributed Ti-Cu layer is a brittle compound with high viscosity and high brittleness, which is unfavorable to the performance of the joint. In the solder composition provided by the present invention, during the soldering process, the Ni-B alloy layer diffuses B atoms outward, and B reacts with Ti in the liquid solder composition in situ to form TiB whiskers, which eventually form a "strong-tough" weld structure in which the TiB whiskers surround the plastic metal as the solder flows. This non-uniform mesh pinning structure of TiB whiskers can coordinate the deformation of the matrix, maintain the strength, and adjust the thermal expansion coefficient of the weld. In the first silver-based solder powder with a Ni-B alloy layer coated on the surface of the present invention, the content of B in the Ni-B alloy layer is 2wt.%~8wt.%; the thickness of the Ni-B alloy layer is 0.1 μm~1 μm; and the particle size of the first silver-based solder powder is 100 mesh~300 mesh.
[0012] The solder composition provided by the present invention includes Ti powder. The particle size of the Ti powder of the present invention is 100 mesh to 300 mesh. In order to make B react with Ti in the liquid solder composition in situ to generate TiB whiskers during the welding process, the present invention must have a certain Ti activity. If the Ti activity is insufficient, TiB2 will be generated, which is a granular boride and cannot play a whisker-like reinforcement effect; in addition, the shell grade of the first silver-based solder powder with a Ni-B alloy layer on the surface is Ni-B alloy, Ni is a strong Ti activity inhibitor, and the Ti activity will be reduced after Ni is dissolved, so Ti supplementation is required.
[0013] The solder composition provided by the present invention further comprises a second silver-based solder powder. The particle size of the second silver-based solder powder of the present invention is 100 mesh to 300 mesh. If the solder composition of the present invention does not add the remaining amount of the second silver-based solder powder, the resulting solder composition will not be melted, and thus cannot be used for welding at all.
[0014] The present invention uses a chemical deposition method to coat a Ni-B alloy layer on the surface of a spherical first silver-based solder powder to form an active solder powder with a core-shell structure. Specifically, the first silver-based solder powder with a Ni-B alloy layer coated on the surface of the present invention is obtained by the following method: the first silver-based solder powder is plated with a chemical plating solution to obtain the first silver-based solder powder with a Ni-B alloy layer coated on the surface; the chemical plating solution includes nickel chloride, ethylenediamine, lead chloride, sodium borohydride and sodium hydroxide.
[0015] Specifically, the present invention uses a chemical plating solution to plate the first silver-based solder powder at a pH of 11 to 13. After the plating is completed, the powder is washed, dried, and sieved with a 100-mesh to 300-mesh filter to obtain the first silver-based solder powder with a Ni-B alloy layer on the surface of the present invention. The chemical plating solution of the present invention includes 25 g / L to 35 g / L nickel chloride, 55 mL / L to 65 mL / L ethylenediamine, 0.04 g / L to 0.08 g / L lead chloride, 0.4 g / L to 0.6 g / L sodium borohydride, and 35 g / L to 45 g / L sodium hydroxide, preferably including 30 g / L nickel chloride, 60 mL / L ethylenediamine, 0.06 g / L lead chloride, 0.5 g / L sodium borohydride, and 40 g / L sodium hydroxide. The plating temperature of the present invention is 80°C to 90°C, and the plating time is 20 min to 60 min.
[0016] The present invention uses a chemical plating solution to plate the first silver-based solder powder, and then activates the surface of the first silver-based solder powder. Specifically, the first silver-based solder powder is etched in H2SO4 at a temperature of 40°C to 70°C for 10 min to 45 min, and the surface activation of the first silver-based solder powder is completed; the H2SO4 is a H2SO4 solution with a concentration of 80 mL / L to 110 mL / L. In certain embodiments of the present invention, a mixed solution of anhydrous ethanol and acetone with a volume ratio of (0.9 to 1.1): (0.9 to 1.1) is used as a cleaning solution to ultrasonically clean the first silver-based solder powder for 4 min to 6 min, dry it, and then etch it in H2SO4 at a temperature of 40°C to 70°C for 10 min to 45 min, and then wash and dry it.
[0017] The present invention also provides a welding method, comprising the following steps: fully mixing a binder and the brazing material composition described in any of the above technical solutions, placing the mixture between the ceramic to be welded and the metal to be welded, and performing heat treatment. Specifically, the binder and the brazing material composition are fully mixed into a paste, and then the paste is placed between the ceramic to be welded and the metal to be welded, and heat treatment is performed under vacuum; the vacuum is 1×10 -3 Pa~5×10 -3 Pa.
[0018] The welding method provided by the present invention is a brazing method, which uses the brazing material composition of the present invention to weld ceramics and metals, and can achieve the improvement of the performance of ceramic-metal welded joints. Specifically, the welding method provided by the present invention, on the one hand, utilizes the spherical first silver-based brazing material powder coated with a Ni-B alloy layer on the surface of the brazing material composition as mentioned above, and spontaneously forms a "strong-tough" type weld structure in which TiB whiskers surround the plastic Ag-based solid solution in situ. This non-uniform mesh pinning structure of TiB whiskers can coordinate matrix deformation, strengthen joints, maintain strength, adjust stress, and adjust the thermal expansion coefficient of the weld. On the other hand, the continuous distribution of larger-sized Ag-based solid solutions can provide plastic deformation sites, passivate cracks, bear strain, and achieve a large degree of plastic deformation. Therefore, the welding method provided by the present invention has the advantages of simple welding process, low residual stress at the joint interface, and high joint strength, and is particularly suitable for welding large-scale and complex-structured ceramic-metal composite components.
[0019] The welding method provided by the present invention utilizes the core-shell structure brazing material in the brazing material composition of the present invention to realize in-situ reaction brazing connection, and by controlling the heat treatment process parameters during welding, including heating rate, brazing temperature, holding time, cooling rate, etc., so as to match it with the in-situ reaction control, a better welding effect can be obtained. The heat treatment of the present invention is specifically: heating to 850℃~920℃ at a heating rate of 10℃ / min~20℃ / min and keeping it for 1 min~30 min, and cooling to room temperature at a cooling rate of 5℃ / min~10℃ / min; wherein room temperature refers to the temperature of indoor air in a normal indoor environment without artificial regulation.
[0020] The present invention discloses a solder composition and a welding method. The solder composition provided by the present invention comprises a core-shell structure active solder powder, Ti powder and silver-based solder powder. The core-shell structure active solder powder is obtained by coating Ni-B alloy particles on the outside of silver-based spherical solder particles. The solder composition of the present invention is used for ceramic-metal welding. On the one hand, during the brazing process, Ti in the solder and B atoms in the Ni-B layer in the solder in situ generate TiB whiskers. The TiB whiskers, as a reinforcing phase, are in situ nucleated and grown in the molten solder. The interface energy between the TiB whiskers and the solder matrix is low, the bonding is good, and other impurities will not be introduced. On the other hand, the core-shell structure component will promote the in-situ generated TiB whiskers to be distributed in a cellular structure. The TiB whiskers are distributed in the outer layer of the cellular structure to form a pinning structure. The joint structure is simple and has good rigidity. The silver-based alloy solder is in the core of the cellular structure and has good plasticity and toughness. This "rigid-tough" structure increases the joint strength and improves the creep performance of the joint. In addition, the stress of the joint is reduced by adjusting the stress of the cellular distributed TiB whiskers and releasing the stress of the plastic deformation of the silver-based alloy solder, which significantly improves the comprehensive mechanical properties of the joint. In summary, the welding method provided by the present invention utilizes the in-situ reaction control and in-situ distribution control of the solder composition during the welding process to achieve the improvement of the performance of the ceramic-metal welded joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a scanning electron microscope image of the solder alloy powder of the present invention;
[0022] Figure 2 The present invention is a scanning electron microscope image of a weld micro-area obtained by brazing using the brazing alloy powder of the present invention. DETAILED DESCRIPTION
[0023] The present invention discloses a solder composition and a soldering method. A person skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the above. It should be particularly noted that all similar substitutions and modifications are obvious to a person skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0024] The present invention will be further described below in conjunction with embodiments:
[0025] Example 1
[0026] Powder cleaning and surface activation: The AgCu eutectic spherical powder with a particle size of 300 mesh was cleaned with a 1:1 volume ratio of anhydrous ethanol-acetone mixed solution, ultrasonic cleaning for 5 minutes, and then dried for use. A H2SO4 solution with a concentration of 100 ml / L was prepared, and the cleaned AgCu powder was added to the prepared H2SO4 solution, and etched at 50°C for 15 minutes to complete the surface activation. The powder was then washed with deionized water and dried for use.
[0027] Chemical deposition of Ni-B alloy: prepare chemical plating solution, the main components of which include 30 g / L nickel chloride, 60 mL / L ethylenediamine, 0.06 g / L lead chloride, 0.5 g / L sodium borohydride and 40 g / L sodium hydroxide, control the pH value to 12, the temperature to 90°C, and the plating time to 30 min. After the Ni-B alloy is plated, wash the powder with deionized water and dry it. Sieve the Ni-B@AgCu solder powder with a 300-mesh filter. Figure 1 As shown, Figure 1 This is a scanning electron microscope image of the solder alloy powder of the present invention. Figure 1 It can be seen that the solder alloy powder of the present invention is a core-shell structure solder powder, the bright spherical powder is an AgCu alloy, and the outer side of the spherical alloy is surrounded by a Ni-B alloy layer with a thickness of about 0.2 μm.
[0028] Preparation of solder alloy powder: Ni-B@AgCu powder, AgCu eutectic powder and Ti powder are mixed in a certain proportion, wherein the content of Ni-B@AgCu powder is 10 wt.%, the content of Ti powder is 5 wt.%, and the balance is AgCu powder. The prepared alloy powder is fully mixed in a powder mixer to obtain solder alloy powder.
[0029] Brazing connection: Mix the prepared brazing alloy powder with glycerol binder to prepare a paste. Place a certain amount of brazing alloy powder between the Al2O3 ceramic and TC4 alloy to be brazed, place the sample in a vacuum brazing furnace, and evacuate to 5×10 -3 Pa, then heated to welding temperature (900℃), kept warm for 5 min, then cooled to room temperature at a cooling rate of 5℃ / min, and finally completed welding. Figure 2 As shown, Figure 2 The micro-area scanning electron microscope image of the weld brazed by using the brazing alloy powder of the present invention shows the cellular structure formed after the core-shell structure brazing alloy is melted.
[0030] Test joint strength: This method is used to braze Al2O3 ceramics and TC4 alloy, and the shear strength of the joint reaches 110±15.8 MPa, which is about 30% higher than the strength of the brazed joint using AgCu brazing filler metal.
[0031] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A solder composition, characterized in that include: 10 wt.% to 40 wt.% of a first silver-based solder powder having a Ni-B alloy layer coated on the surface; 1 wt.%~5 wt.% Ti powder; the balance of the second silver-based solder powder; The first silver-based solder powder and the second silver-based solder powder are independently selected from one or more of AgCu or AgCuTi.
2. The solder composition according to claim 1, characterized in that The first silver-based solder powder and the second silver-based solder powder are both selected from AgCu; or, the first silver-based solder powder and the second silver-based solder powder are both selected from AgCuTi.
3. The solder composition according to claim 1, characterized in that The content of B in the Ni—B alloy layer is 2 wt.% to 8 wt.%.
4. The solder composition according to claim 1, characterized in that The particle size of the first silver-based solder powder is 100-300 mesh; the thickness of the Ni-B alloy layer is 0.1 μm-1 μm; The particle size of the second silver-based solder powder is 100 mesh to 300 mesh; The particle size of the Ti powder is 100-300 mesh.
5. The solder composition according to any one of claims 1 to 4, characterized in that The first silver-based solder powder with a Ni-B alloy layer coated on the surface is obtained by the following method: Plating the first silver-based solder powder with a chemical plating solution to obtain the first silver-based solder powder with a Ni-B alloy layer coated on the surface; The chemical plating solution comprises nickel chloride, ethylenediamine, lead chloride, sodium borohydride and sodium hydroxide.
6. The solder composition according to claim 5, characterized in that The chemical plating solution includes 25 g / L to 35 g / L of nickel chloride, 55 mL / L to 65 mL / L of ethylenediamine, 0.04 g / L to 0.08 g / L of lead chloride, 0.4 g / L to 0.6 g / L of sodium borohydride and 35 g / L to 45 g / L of sodium hydroxide.
7. The solder composition according to claim 5, characterized in that The plating is performed at a pH of 11 to 13, the plating temperature is 80° C. to 90° C., and the plating time is 20 min to 60 min.
8. The solder composition according to claim 5, characterized in that Before plating, the first silver-based solder powder is etched in H2SO4 at a temperature of 40°C to 70°C for 10 min to 45 min.
9. A welding method, characterized in that: The following steps are involved: The binder and the brazing material composition according to any one of claims 1 to 8 are placed between the ceramic to be welded and the metal to be welded, and heat treatment is performed.
10. The welding method according to claim 9, characterized in that: The heat treatment is performed under vacuum, and the heat treatment is specifically as follows: heating to 850°C~920°C at a heating rate of 10°C / min~20°C / min, keeping the temperature for 1 min~30 min, and cooling to room temperature at a cooling rate of 5°C / min~10°C / min.
Citation Information
Cited By
Composite silver-copper brazing filler metal, soldering paste and preparation method and brazing method of composite silver-copper brazing filler metal and soldering paste
CN121468009A
Flux-cored wire for dissimilar welding of high-strength weathering resistant steel and ordinary steel and application of flux-cored wire
CN121491602A